Assessing the Impact of Instructional Video Clips in the Training of Bread Production - Metty Muhariati; Nurlaila Nurlaila; Mahdiyah Mahdiyah (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The main objective of this study was to investigate the effectiveness of instructional video clips as the learning media in the training of sweet bread production for the members of Family Welfare Movement in Rawamangun, Jakarta Timur. The data were analysed using qualitative descriptive analysis. The results showed that video clips implied the learning improvement of 32.5 categorized as significant which was analysed  from the scores of the pretest and the posttest. The data requirements tests using Liliefors indicated abnormal data thus the data were tested using a non-parametric test, namely Wilcoxon test resulting the score of 0,001. Therefore the decision was to accept H1 hypothesis suggesting a significant difference between the pretest and the posttest. Video clips were confirmed to be effective in the learning process based on the interval scale of effectiveness for the posttest score which achieved the score of 79 categorized as E or effective.